2019–2020 Florida Citrus Production Guide: Citrus Cold Protection - Tripti Vashisth; W. Chris Oswalt (EDIS, 2019)
No other single factor has affected the historical distribution of Florida citrus more than freezing temperatures. Since the introduction of citrus by the Spanish in the 1500s, freezing temperatures have dictated where the citrus production areas in Florida are located. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Chris Oswalt and Tripti Vashisth, and published by the Horticultural Sciences Department, March 2019.